Studi Kestabilan Fisika Dan Kimia Dispersi Padat Ketoprofen -Urea - Salman Umar; Monica Selfia; Rieke Azhar (STIFARM Padang, 2014)
A research on the study of physical and chemical stability of ketoprofen-urea solid dispersions. Solid dispersions prepared through dissolution method with ketoprofen-urea ratio is 1:1, 1:3, 1:5. Powder solid dispersion system was evaluated physicochemical properties include analysis Differential Thermal Analysis (DTA), FT-IR spectroscopy, and dissolution profiles. Accelerated stability test for 3 months at a temperature (40±2)°C. The parameters tested include organoleptic test and ketoprofen levels. Ketoprofen levels were measured by UV spectrophotometer at a wavelength of 255.5 nm after being stored for 1, 2, and 3 months at a temperature (40±2)°C. DTA analysis results showed endothermic peak shift ketoprofen meaningful. FT-IR spectra showed no chemical interaction between ketoprofen-urea solid dispersion powder. The results showed that solid dispersions of ketoprofen-urea can improve the physicochemical properties and can enhance the dissolution profile of solid dispersion compared to pure ketoprofen with the highest dissolution results indicated by solid dispersion formula 3 (1:5) is 105.674%. Test chemical and physical stability of solid dispersions of ketoprofen-urea showed a change in the physics and chemistry of solid dispersions. Organoleptic test the change in color the three formulas. While the test by the chemical assay, the three formulas while showed that increasing the concentration of urea in the solid dispersion of a decrease in the levels of ketoprofen. The most stable formula is the formula 1 (1:1) to 24.748 months of age.